Light beam induced finger instability in a photosensitive liquid crystal cell - Ignacio Andrade-Silva; Marcel G. Clerc; Gregorio Gonzalez-Cortes; Vincent Odent (Physical Review Research, 2021)
Interfaces limiting two phases in driven systems may exhibit rich dynamical behaviors. Optically induced phase transitions are of particular interest for the study of interfacial phenomena. Dye-doped liquid crystals offer an ideal scenario in which phase transitions can be induced by purely optical means. Light-driven interface dynamics and spatial structure have been partially unveiled. Here we report the emergence of fingerlike structures at the nematic-isotropic interface in a photoisomerization experiment. A reduced model reveals the instability origin, which is derived from a model for the dopant concentration and the order parameter. Analogously to the hydrodynamically triggered finger instability, the interdigital space follows a power law. When the cell is in the isotropic phase and the light turns off, transient foamlike and labyrinthine textures are observed. Numerical simulations reproduce the observed behaviors. Our findings open an avenue for optically addressed interfacial dynamics and shape tailoring of spatial textures, not only liquid crystals but also polymers.